Customer centered service in Malaysia: a case study in Malaysian public universities / Nor Hapiza Mohd Ariffin and Norfarizan Mohd Daud - Mohd Ariffin, Nor Hapiza; Mohd Daud, Norfarizan (Universiti Teknologi MARA Press (Penerbit UiTM), 2019)
The Information and Communication Technology (ICT) represents a basis for the development of the academic institution in public sector. Thus, there is a huge change emerging from the traditional academic institution into technological environment based. ICT implementations indirectly will represent the major changes of the business processes. In term of providing the best ICT facilities and infrastructure, there are often an issue about service delivering, customer expectation, utilization of infrastructure, knowledge sharing and any matters regarding ICT services. Therefore, this study was conducted to analyze the adoption of customer centered service for ICT services in Malaysian public university. There are two main objectives of this study which first, to identify the current status of customer centered service for ICT services and second, to identify the impact of adoption customer centered service for ICT services. Ten (10) public universities in Malaysia were involved in this study. A survey using interview and questionnaires was used for collecting data. The findings showed that 80% of public universities in Malaysia have adopted centered customer services to facilitate the ICT services and facilities in their universities and this study revealed the positive impact of customer centered service to the ICT services. Suggestions as to what future research should indicate are also discussed.